Enhancing catalytic durability in alkaline oxygen evolution reaction through squaric acid anion intercalation - Ruoyao Fan; Shanshan Lu; Fuli Wang; Yusheng Zhang; Mirabbos Hojamberdiev; Yongming Chai; Bin Dong; Bin Zhang (Nature Communications)
Abstract The corrosive acidic interfacial microenvironment caused by rapid multi-step deprotonation of alkaline oxygen evolution reaction in industrial high current water electrolysis is one of the key problems limiting its stability. Some functional anions derived from electrocatalysis exhibit special functionalities in modulating the interface microenvironment, but this matter has not received adequate attention in academic discussions. Here we show that the coordinate squaric acid undergoes a dissolve-re-intercalation process in alkaline oxygen evolution, leading to its stabilization within the Fe-doped NiOOH interlayer in the form of the squaric acid anions (NiFe-SQ/NF-R). These intercalated squaric acid anions stabilizes OH− through multiple hydrogen bond interactions, which is conducive to maintaining high catalytic interface alkalinity. Hence, the interfacial acidification of prepared NiFe-SQ/NF-R is inhibited, resulting in a tenfold prolong in its catalytic durability (from 65 to 700 h) when exposed to 3.0 A cm−2, as opposed to NiFe-LDH/NF-R. This derived functional anion guarantees the enduring performance of the NiFe-derived electrocatalyst under high current densities by controlling the interfacial alkalinity.